“An Experimental Evaluation Of Shanapushpi (Crotalaria verrucosa L.) For Its Antipyretic Property” - Patagar, Raghavendra Laxman; Rao S, Ravi; P , Subramanya (International Research Journal of Ayurveda & Yoga, 2024)
Current study was carried out to evaluate the antipyretic activity of Crotalaria verrucosa L. plants in Brewer’s yeast induced pyrexia in Albino rats. Brewer’s yeast solution was injected subcutaneously at the region of thigh in all the rats in the dose of 1ml/100gms body weight.After 1 hour of injection of yeast, corresponding test drug was administered for all the groups. Rats of Group 1 which was administered with distilled water 1ml/100gms of body weight. Animals of Group 2 were administered with paracetamol suspension at the dose of 0.75ml/100gm of the body weight by using feeding syringe. Similarly rats of Group 3 were administered with decoction of trail drug at the dose of 1ml/100grms of body weight. After administering corresponding drugs to each group hourly rectal temperature of each rat was noted till successive 14 hours. The result was analysed statisticallywith repeated measures of one way ANOVA test.The analysis suggested that the Shanapushpi (Crotalaria verrucosa L.) had significant antipyretic activity.